Musculotendinous Disorders in the Lower Leg - Newman, Joel S. (Seminars in Musculoskeletal Radiology, 2017)
Musculotendinous injury in the lower leg is associated with a variety of athletic activities. Myotendinous strain is typically localized to the posterior calf muscles, with involvement of the medial head of gastrocnemius muscle most common. Nontraumatic soft tissue injuries of the lower leg, including muscle herniation, are less frequently imaged. Ruptured popliteal cysts and deep vein thrombosis are important differential considerations in the patient presenting with acute calf pain and swelling.
Keywords: calf muscle injury; magnetic resonance imaging; ultrasound; popliteal cyst rupture; calf deep vein thrombosis